Knowledge, Attitude and Practice Related to HIV/AIDS Prevention Among Secondary School Students in Klang, Malaysia - Mohammadi, Mahtab (2010)
The HIV/AIDS has killed more than 25 million people since it was first recognized in 1981, making it one of the most destructive pandemics in recorded history. The adolescents generally tend to have high levels of knowledge about the meaning of HIV transmission, however somewhat lower levels of knowledge about effective means of protection lack some critical information and hold a number of misconceptions about the risks associated with casual contact. Knowledge about HIV/AIDS is clearly important for young people to prevent behaviors that place them at risk of contracting HIV, however, knowledge itself, is not necessarily associated with HIV preventive actions such as condom use. The aim of this study was to determine the level of knowledge, attitude and practices related to HIV/AIDS prevention among secondary school students in Klang district. A cross-sectional study design was used. The study population was secondary school students in Klang district. Data was collected from 9th of February to 28th of March 2009 using a pre-tested self-administrated (Bahasa Malaysia) questionnaire. Data was analyzed using SPSS version 16.0. Out of the 2273 students; 61.7% were male. Majority were Malays (37.2%) followed by Chinese (35.7%) and Indians (26.0%). The mean age ranged from 14 to 18 years. The overall mean age among the males (15.48 SD ±1.14 years) was not significantly different from that of the females (15.49 SD ±0.04 years) (t = -0.26, df = 2271, p>0.05). The main sources of information for HIV/AIDS awareness reported by the respondents were the print media (62.3%). The overall mean knowledge score of the respondents was 7.01 (SD ±3.62) and ranged from 0 to 15 points. One hundred and eighteen students 5.2% obtained 0 (zero) marks in knowledge questions score and 88.8% of students had less than 75% of full marks in knowledge question score. The result of this study revealed that although the majority (77.7%) of students knew that AIDS is fatal disease almost 52% were not aware that there is no cure for AIDS and only 23.7% knew that there is no vaccine that can stop people from getting HIV. More than half of the participants believed that HIV transmission was possible through casual contact with HIV-positive persons, such as sharing food (68.6%), sharing a glass of water (71.1%) and from mosquito bites (60.4%). Abstaining from sexual intercourse, having one uninfected faithful sex partner and use of condoms as an HIV prevention measure was not well understood among the participants, as indicated by an incorrect response rate of 55.7%, 63.5% and 67.2% respectively. Mean attitude score toward HIV/AIDS was 25.32 (SD ±3.60) and ranged from 8 to 45 points. Mean practice score regarding HIV/AIDS was 4.53 (SD ±1.063) and ranged from 0 to 6 points and mean sexual behavior score was 3.73 (SD ±0.78) and ranged from 0 to 6 points. The results also showed that knowledge of respondents was significantly associated with age (F =33.41, p = 0.001) and academic grade (F = 31.47, p = 0.001). Attitude related to HIV/AIDS was significantly associated with age (F = 10.52, p = 0.001), mother’s education (F = 2.87, p = 0.035) and academic grade (F = 21.03, p = 0.002). The practice of respondents related to HIV/AIDS was significantly associated with gender (F = 153.95, p = 0.001), age (F = 9.32, p = 0.001), religion (F = 2.82, p = 0.024), family income (F = 2.88, p = 0.035) and academic grade (F = 4.56, p = 0.001). In conclusion, the result of study showed that the level of knowledge related to HIV/AIDS among secondary school students in Klang is not satisfactory. There is considerable misconception regarding transmission and prevention of HIV/AIDS. The respondents seem to have unfavorable attitude on the prevention of HIV/AIDS. Among 6.1% of students that admitted to have ever had sexual intercourse, only 43.1% of them reported that they or their partners used condom at last sexual intercourse. It is recommended that peer-led intervention on improvement of knowledge, attitudes and behaviour of secondary school children related to HIV prevention be implemented.